2019
DOI: 10.12688/f1000research.16576.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the understanding and management of erectile dysfunction

Abstract: Erectile dysfunction (ED) is important to a man’s well-being and health, since it not only affects the individual but also causes strain on a couple’s lifestyle and relationship. There are multiple non-invasive treatments that exist for ED including lifestyle changes, oral medications (phosphodiesterase type 5 inhibitors), vacuum-assisted erectile devices, and intraurethral suppositories. While lifestyle changes and oral medications are typically first-line treatments for ED, more-invasive treatments including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 42 publications
0
39
0
4
Order By: Relevance
“…In addition, intraurethral suppositories, vacuumsupported erectile devices, and penile prostheses are other treatment options. 27 Regenerative treatments that aim not only to treat symptoms but also to restore the structure and function of the diseased erectile tissue are new treatment options for ED. 31 They allow long-term preservation of erectile function through a regenerative model that induces both nerve and muscle cell regeneration by regulating growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intraurethral suppositories, vacuumsupported erectile devices, and penile prostheses are other treatment options. 27 Regenerative treatments that aim not only to treat symptoms but also to restore the structure and function of the diseased erectile tissue are new treatment options for ED. 31 They allow long-term preservation of erectile function through a regenerative model that induces both nerve and muscle cell regeneration by regulating growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Согласно рекомендациям Американской урологической ассоциации (American Urological Association), любой вариант лечения ЭД может использоваться в качестве терапии 1-й линии [22]. Варианты лечения ЭД в настоящее время включают изменение образа жизни, терапию локальным отрицательным давлением, пероральную фармакотерапию ингибиторами фосфодиэстеразы 5-ФДЭ-5 (силденафил, варденафил, тадалафил и аванафил), интракавернозные инъекции вазоактивных препаратов (алпростадил, папаверин), фаллопротезирование, а также более новые подходы, такие как: имплантация наружного пенильного протеза [23][24][25][26], методики микрохирургической реваскуляризации, рентгенэндоваскулярные технологии [23,[26][27] и реконструкции кавернозного нервного трансплантата [27]. Недавно во Франции был разрешен к применению крем «Алпростадил» (Vitaros), сочетающий активную молекулу с усилителем кожи.…”
Section: лечение эректильной дисфункции у больных с хронической болезнью почекunclassified
“…The two main changes in sexual function with age in men are erectile dysfunction and ejaculatory dysfunction. It has been suggested that erectile dysfunction occurs in around 50% of men over the age of 70 and is mediated by psychological and physiological factors; the most important risk factors include age, obesity, smoking, coronary artery disease and depression (Krzastek 2019). The most common treatments for this disorder are lifestyle changes to reduce vascular risk factors (e.g.…”
Section: Menmentioning
confidence: 99%
“…The most common treatments for this disorder are lifestyle changes to reduce vascular risk factors (e.g. stopping smoking, losing weight) and oral vasodilating phosphodiesterase type-5 inhibitors, which act to increase blood flow to the penis (Krzastek 2019). Newer techniques include intracavernous injections of prostaglandin E1 and penile implant surgery (Rajpurkar 2003).…”
Section: Menmentioning
confidence: 99%